Mergers and Acquisitions in India - Agarwal, Ankita (2009)
From the past few decades, Mergers and Acquisitions (M&A) have dominated the environment in which the companies operate. Whenever there is an announcement about a merger, there is an excitement and expectation among the shareholders. This expectation may or may not convert into an abnormal return. It is useful to have some kind of research activity on the performance of M&A, as both bidders and target firms will gain from it. The results have revealed that on average, the returns to the target companies are positive and that they gain from mergers. However, the bidder returns may be zero or negative, but it turns out be a different story in the long run.